PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF “LENTERA” UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Aprilia, Elsa; Afandi, Muhamad (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
This study aims to develop an interactive learning media “Lentera” and examine its feasibility and effectiveness in improving elementary students’ critical thinking skills. The research is motivated by the low level of students’ critical thinking due to conventional teaching methods and limited use of interactive media. This study employs a Research and Development (R&D) method using the ADDIE model. Data were collected through questionnaires, observations, and critical thinking tests. The results show that the “Lentera” media is highly feasible and effective in improving students’ critical thinking skills. Therefore, it can be used as an innovative learning alternative in elementary education.